Numerical study of evaporation–condensation heat transfer in finned double pipe heat exchangers - Junrong Yang; Tianming Zhong; Xin Yan; Haokun Li; Zhilin He; Haoxian Bai; Shiwen Fang (Case Studies in Thermal Engineering)
Double pipe heat exchangers (DPHEs) are widely used in industrial fields, such as refrigeration, heat pumps, and chemical industry, owing to their efficient coupled heat transfer characteristics of evaporation and condensation. In this study, the effects of inner and outer tube diameter combinations and inlet velocity on heat transfer performance, pressure drop, and thermal performance are systematically analyzed through computational fluid dynamic simulation. Results show a significant difference in heat transfer performance under different conditions. At an inlet velocity of 2 ms−1, the total heat transfer coefficient of Case 5 is 66.1 % higher than that of Case 2. Case 3 has the lowest pressure drop among all the cases. Turbulence increases interface renewal, mixing efficiency, and heat transfer efficiency when the inlet velocity is 8 ms−1. When the velocity is 2 ms−1, turbulence is reduced, and the gravity effect dominates across, resulting in a drop in heat transfer efficiency. This study reveals the influence law of inner and outer tube diameters and flow velocity on the coupled heat transfer characteristics, which provides an important theoretical basis and a practical reference for optimizing the design of DPHEs and has significant application in heat-intensive industries.